2018
DOI: 10.1080/01676830.2018.1466901
|View full text |Cite
|
Sign up to set email alerts
|

The microbiologic profile of dacryocystitis

Abstract: Given the broad range of causative organisms, routine treatment of dacryocystitis with any specific antibiotic may fail in up to one-third of patients. Obtaining a culture at the time empiric antibiotic treatment is initiated can prove extremely valuable when treating patients with dacryocystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 32 publications
8
28
4
Order By: Relevance
“…The female-to-male ratio of this study was 1.11, which is signi cantly lower than the previous results [14][15][16]. The reason for this difference might be that the major (105/169) included subjects of this study were pediatrics, with overall mean age of 16.6 years old, while the previous studies included more adult than pediatrics in their studies, with mean age of from 44 to 60 years old [14][15][16]. Apart from pediatric group, the female-to-male ratio in adult group could increase to 2.56 in this study, which was consistent with the reported values of previous studies [14][15][16].…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…The female-to-male ratio of this study was 1.11, which is signi cantly lower than the previous results [14][15][16]. The reason for this difference might be that the major (105/169) included subjects of this study were pediatrics, with overall mean age of 16.6 years old, while the previous studies included more adult than pediatrics in their studies, with mean age of from 44 to 60 years old [14][15][16]. Apart from pediatric group, the female-to-male ratio in adult group could increase to 2.56 in this study, which was consistent with the reported values of previous studies [14][15][16].…”
Section: Discussioncontrasting
confidence: 88%
“…Previous studies have reported that the pathogens in dacryocystitis were similar to those found in the upper respiratory passage and on the skin [2,16]. However, the application of broad-spectrum antibiotics might have an in uence on the microbiologic spectrum of dacryocystitis [17].…”
Section: Introductionmentioning
confidence: 97%
“…Mills et al [1] reported that the rate of MRSA in dacryocystitis cases is 21.7%. This rate was 20% in a study by Chung et al [2] and 42.2% in the ARMOR surveillance study [21]. In this study, the most effective antibiotics for Staphylococcus spp.…”
Section: Discussionmentioning
confidence: 56%
“…Although treatment guidelines recommend bacterial culture testing in patients with dacryocystitis, empirical antibiotic treatment is generally preferred [6,7]. However, the microbial spectrum of chronic dacryocystitis may change over time and lead to treatment failures [2,8]. Therefore, identification and antibiotic susceptibilities of microorganisms should be determined in patients with dacryocystitis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous study has reported that the pathogens in dacryocystitis were similar to those found in the upper respiratory passage and on the skin [2,16]. However, the application of broad-spectrum antibiotics might have an in uence on the microbiologic spectrum of dacryocystitis [17].…”
Section: Introductionmentioning
confidence: 96%